The Role of IL-36 in Infectious Diseases: Potential Target for COVID-19? - Wang, Xiaofang; Yi, Panpan; Liang, Yuejin (Frontiers in Immunology, 2021)
IL-36 is a member of the interleukin 1 cytokine family, which is currently experiencing a renaissance due to the growing understanding of its context-dependent roles and advances in our understanding of the inflammatory response. The immunological role of IL-36 has revealed its profound and indispensable functional roles in psoriasis, as well as in several inflammatory diseases, including inflammatory bowel disease (IBD), systemic lupus erythematosus, rheumatoid arthritis (RA) and cancer. More recently, an increasing body of evidence suggests that IL-36 plays a crucial role in viral, bacterial and fungal infections. There is a growing interest as to whether IL-36 contributes to host protective immune responses against infection as well as the potential implications of IL-36 for the development of new therapeutic strategies. In this review, we summarize the recent progress in understanding cellular expression, regulatory mechanisms and biological roles of IL-36 in infectious diseases, which suggest more specific strategies to maneuver IL-36 as a diagnostic or therapeutic target, especially in COVID-19.